Mandibular bone necrosis after use of paraformaldehyde-containing paste - Chi-hwan Lee; Yoorina Choi; Sujung Park (Korean Academy of Conservative Dentistry, 2016)
Paraformaldehyde has been used in the past as a pulpotomy agent. However, it has a severe cytotoxic effect and may cause alveolar bone necrosis. Depulpin, a devitalizing agent containing 49% paraformaldehyde, is no longer used frequently due to its severe side effects. In the two cases described in the present study, Depulpin was used as a devitalizing agent during root canal treatment. It caused a gradual loss of sensibility in adjacent teeth, gingival necrosis, and osteomyelitis. This case report demonstrates the serious side effects of using a paraformaldehyde-containing paste as a devitalizing agent for pulp, particularly mandibular bone necrosis.